Pengaruh Layanan Food Delivery Terhadap Peningkatan Penjualan Usaha Kuliner (Studi Terhadap Pemilik Usaha Kuliner Yang Terdaftar Go-Food Di Kelurahan Jagir Kota Surabaya) - Muhammad Irham Hafiyyan; Mauren Gita Miranti; Mein Kharnolis; Asrul Bahar (Student Research Journal, 2023)
This Research to determine the effect of Go food services on whether or not sales of food outlets in the Jagir Village increase or not. This study uses quantitative research methods with the type of field research (Field Research). The results of the study show that the existence of the Go Food application used by culinary business sellers has a positive influence on increasing sales. So with an increase in income turnover, it is not impossible that they will continue to use Go Food. The results of the calculation of the t test by looking at the significance number show the sig value. of 0.004 alpha 0.05. Then Ha is accepted and Ho is rejected, which means that there is a significant effect between Go-food services on increasing sales of culinary entrepreneurs in Jagir Village.